IMPROVING STUDENTS’ WRITING NARRATIVE TEXT BY USING CHAIN STORY TECHNIQUE - Suryani, Yatni; Sutapa Y, Y. Gatot; Rezeki, Yanti Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The aim of this study was to improve the students’ writing narrative text using chain story technique to the tenth grade students of SMAN 1 Sungai Ambawang in academic year 2017/2018. In this research, the researcher used chain story as the technique to solve the students’ problems. The method of this research was classroom action research in three cycles. Through Observation checklist, field note and writing assessment the data was collected. The subject of the research was thirty one students of tenth grade science students. The findings showed that during teaching and learning process, the students more confident in writing and enthusiastic followed the activity in the classroom. The chain story technique could also improve students writing narrative text. This could be seen from the improvement of students in writing narrative text based on its generic structures, the students could differentiate the generic structure of narrative text. In addition, the students also improved their abilities in using simple past tense correctly. It can be concluded that the use of chain story technique improved the students writing narrative text.Keywords: Chain Story Technique, X IPA of SMAN 1 Sungai Ambawang, writing narrative text, Classroom Action Research.